Assessing Audit Quality's Impact on The Connections Between Profit Management and Free Cash Flow - Rahim Jafar Mahammad Sharif (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The most objective of this inquire about is to consider the impact of quality of examining on the relationship between the free cash stream and the benefit administration within the companies conceded into Tehran Stocks Trade. In arrange to reply this address, a test measure of 88 companies conceded into Tehran Stocks Trade amid the long time2011-2021 was considered. Two measures of the number of auditors and the extent of the auditors' industry specialization were used in this investigation and in terms of the inspecting quality variable. In arrange to test the results about theories; the relapse models at a noteworthy level of 95% were utilized. The findings demonstrated that for the most part there's a noteworthy connection between the benefit administration and free cash stream. In taking after the investigate, the effect of two metrics of auditors' quantity and industry-specific specialty and at long last the impact of examining quality on the connections between the free cash stream and profit administration within the companies conceded into Tehran Stocks Trade were examined as well. Agreeing to the comes about, it was uncovered that there's noteworthy and coordinate connections between the free cash stream and benefitadministration and an roundabout (switch) critical connections between the quality of inspecting and the connections between the free cash stream and benefit administration. It implies that the quality of reviewing can weaken the connections between the free cash stream and benefit administration.